THE ROLE OF READING ALOUD STRATEGY ON IMPROVING READING AND PRONUNCIATION FOR EFL PUPILS AT PRIVATE BASIC SCHOOLS: TEACHERS PERSPECTIVES - Abbas Mukhar Mohamed Badawi; Nagla Taha Bashrie Alnour; Montaser Alamin; Sami Balla Sanhori (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
The study aims at investigating the role of reading aloud on English as foreign language for learners in improving reading and pronunciation at basic level schools. The study used the descriptive analytical method. In order to examine the hypotheses, the study used a questionnaire as a tool for collecting needed data. The questionnaire was distributed randomly to fifty English language teachers at private schools in Bahary locality. The data was analyzed by using SPSS program. The study came up with results that reading aloud is beneficial to develop and promote pupils reading, as well as improving their pronunciation. The study mentioned some recommendations and suggested some points of studies which can convene futurity.